Kondisi Sosiokultural yang Mempengaruhi Pemanfaatan Bantuan PKH di Nagari Sungai Sariak - Ihsan, Shahibul; Syahrizal, Syahrizal; Meiyenti, Sri (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2024)
The Family Hope Program (PKH) requires aid recipients to utilize the aid received in the education and/or health sectors. However, in implementation, there are still various ways of utilizing aid, this is due to the different socio-cultural conditions in each community. This research aims to determine the sociocultural conditions that influence how PKH assistance is utilized. The research was conducted in Nagari Sungai Sariak, one of the Nagari in Padang Pariaman Regency which has the most recipients of PKH assistance. This research uses qualitative research methods and a case study approach, and collects data by means of observation and interviews. The results of this research show various ways of using aid in nagari, some are used to meet educational and health needs, but there are also many other ways, such as buying rice or even buying clothes. This is because of the socio-cultural conditions in the nagari, in the form of the wife having more power at home, so the management of aid is controlled by the wife.